Determination of settlement limit values for a new concrete box subgrade with ballasted track. (November 2022) - Zhu, Zhihui; Qin, Yu; Wang, Kun; Gong, Wei; Zheng, Weiqi
Highlights: The influences of ground settlement on track deformation, force and vehicle dynamic responses are investigated. A real-time co-simulation solution which considers the nonlinearity of voided sleepers is adopted. The settlement limit values of ballasted track-concrete box subgrade are obtained. Abstract: To obtain the settlement limits of ballasted track-concrete box subgrade (BTCBS), the influences of ground settlement on track deformation, force and vehicle dynamic responses are investigated in this paper. Firstly, the new type of BTCBS structure is introduced, and four settlement types are proposed according to the structural characteristics, including box faulting, trapezoid settlement, V-shape settlement and box rolling. Then, the influences of ground settlement on track deformation and fastener force are investigated based on the nonlinear finite element model of BTCBS. Furthermore, based on the train-ballasted track-concrete box subgrade (TBTCBS) dynamic model, the influences of settlement on train dynamic responses are studied by adopting a real-time co-simulation method which considers the nonlinearity of voided sleepers. On this basis, the settlement thresholds of BTCBS are determined according to China's codes. Numerical results show that except that the settlement threshold with box faulting at the speed of 350 km/h is determined by wheel unloading rate, the settlement thresholds of all the other settlement conditions are controlled by 10 m chord versine of vertical irregularity. The settlement thresholds of BTCBS with box faulting, trapezoid settlement, V-shape settlement and box rolling are suggested as 4.02 mm, 17.63 mm, 9.17 mm and 5.53 mm, respectively.